Análise da deformação dinâmica de um contator eletromecânico utilizando redes de Bragg em fibra óptica - Galon, Jean Carlos (2018)
The electromechanical contactors are widely used in industrial environment to connect and disconnect of power load circuits. Due to its variety of applications it is important to guarantee its operation, even in adverse conditions such as voltage sags. The measurement of the dynamic strain of the contactor core can be used to analyze its operation, since the electromagnetic force, that causes the strain, depends on contactor´s voltage and current. The fiber Bragg gratings sensors can be used for contactor core strain measurement due to its electromagnetic immunity and small size. Measurements obtained during tests of contactor´s turn on, steady state and contactor turn off shows the dynamic strain due to electromagnetic forces. Both parts of the electromagnetic forces, constant and sinusoidal, can be observed on the strain curves. The sinusoidal part has a fundamental frequency of 120 Hz, twice of the frequency supply. This work presents results that make feasible the use of FBG sensors for the analysis of electromechanical contactors.